Respondent Incentives in a National Face-to-face Survey: Do They Affect Response Quality?. Issue 3 (August 2016) - Grauenhorst, Thomas; Blohm, Michael; Koch, Achim
Respondent incentives are a popular instrument to achieve higher response rates in surveys. However, the use of incentives is still a controversial topic in the methodological literature with regard to the possible reduction or increase in response quality. We conducted an experiment in a large-scale German face-to-face study in which the treatment group was promised a modest monetary incentive. We used different indicators of response quality and compared the incentivized group with the control group. Our results indicate that in general there are no systematic differences between the incentivized and the control group concerning response quality. We found some hints that specific subgroups react differently to incentives in terms of response behavior. While response quality usually tends to be lower for older respondents, we found that in the incentivized group the response quality is higher for older respondents as compared to younger ones regarding the level of item nonresponse.